Answer:
The output value increases by a factor of 2 as each input value increases by 1.
Step-by-step explanation:
Given:
Function [tex]f(x)[/tex] is an exponential function.
The factor by which [tex]f(x)[/tex] increases with increase in [tex]x[/tex] is same as finding the ratio of two consecutive output values.
When [tex]x[/tex] increases from -4 to -2, [tex]f(x)[/tex] increases from [tex]\frac{3}{16}\ to\ \frac{3}{4}[/tex]. Therefore, the factor by which the output changes is:
[tex]r=\frac{\frac{3}{4}}{\frac{3}{16}} =\frac{3}{4}\times \frac{16}{3}=4[/tex]
The increase in input value for increasing output value by a factor 4 is given as:
[tex]\Delta x=-2-(-4)=-2+4=2[/tex]
So, with the increase of input value by 2, the output value increases by a factor of 4.
Therefore, with the increase of input value by 1, the output values increases by a factor [tex]\frac{4}{2}=2[/tex]
Thus, the output value increases by a factor of 2 as each input value increases by 1.